Green antimicrobial coating based on quaternised chitosan/organic montmorillonite/Ag NPs nanocomposites. Issue 17 (21st November 2016) - Chen, Kaihang; Ye, Weijie; Cai, Shaoling; Huang, Lin; Zhong, Tongsu; Chen, Like; Wang, Xiaoying
ABSTRACT: This work is aimed at developing a green antimicrobial coating. First, a green antimicrobial agent, quaternised chitosan (QCS)/organic montmorillonite (OMMT)/silver nanoparticles (Ag NPs) (QOMA) nanocomposite was fabricated through an environmental-friendly one-step approach. Morphological and structural characteristics of QOMA were investigated, and good antimicrobial activity was proved. QOMA was then incorporated into powder coating formulations to form a homogeneous coating on steel plates, which was studied by scanning electron images. Besides, the physical and mechanical properties as well as the antimicrobial performances of the coatings were discussed. The results showed that the addition of QOMA imparted good antimicrobial capacity to the powder coating, but did not affect its physical and mechanical properties. The coatings were able to effectively inactivate Gram-negative bacteria ( Escherichia coli ), Gram-positive bacteria ( Staphylococcus aureus ) and fungi ( Aspergillus niger, Penicillium funiculosum, Chaetomium globasum, Paecilomyces varioti, Asp . terreus and Aureobasidium pullulans ). Our findings demonstrate the possibilities of green antimicrobial coating containing QOMA for practical applications in medical devices, domestic appliances and other solid surfaces concerning bacterial infection and contamination.